2015
DOI: 10.1007/s12665-014-3705-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of fully coupled finite element analysis of nonlinear hydraulic properties in land subsidence due to groundwater pumping

Abstract: A fully coupled mathematical model of land subsidence caused by groundwater pumping was established based on the mechanics of porous seepage and the theory of fluid-solid interaction. The mathematical model employing the Galerkin finite element method was proposed to simulate the deformation dependencies of hydraulic properties due to the water pressure decrease in aquifers. This model has been verified by comparing with the known analytical solutions in the confined aquifer. Results show that the simulated dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It can be seen from Figure 14 and Table 4 that there exists a significantly positive mean error, indicating that the direct leveling-based subsidences are greater than the predicted ones. This is probably because the ground subsidence induced a decline of the water table, and thus produced an additional subsidence in the ground [36]. The average of the absolute deviations of the proposed method-based subsidence predictions is 2.49 cm, and the maximum of the absolute deviation is 4.05 cm, which is equal to 0.75% of the maximum direct According to the previously observed data in the southern No.1 district of the coal mine, the subsidence prediction parameters could be obtained, including the subsidence factor (0.83), the tangent of the main effect angle (2.0), and the inflection point offset coefficient (0.05).…”
Section: Validation Using Direct Leveling Based Subsidence Observationsmentioning
confidence: 99%
“…It can be seen from Figure 14 and Table 4 that there exists a significantly positive mean error, indicating that the direct leveling-based subsidences are greater than the predicted ones. This is probably because the ground subsidence induced a decline of the water table, and thus produced an additional subsidence in the ground [36]. The average of the absolute deviations of the proposed method-based subsidence predictions is 2.49 cm, and the maximum of the absolute deviation is 4.05 cm, which is equal to 0.75% of the maximum direct According to the previously observed data in the southern No.1 district of the coal mine, the subsidence prediction parameters could be obtained, including the subsidence factor (0.83), the tangent of the main effect angle (2.0), and the inflection point offset coefficient (0.05).…”
Section: Validation Using Direct Leveling Based Subsidence Observationsmentioning
confidence: 99%
“…In addition, numerical modeling studies which included stress dependent hydraulic parameters showed that groundwater pumping could reduce permeability by sediment compaction that could delay the hydraulic response, and hence, could slow down subsidence rates (Kim and Parizek 1999;Ortega-Guerrero et al 1999). However, near the vicinity of pumping wells, subsidence rates could increase due to the gradual rise in hydraulic gradient from permeability reduction (Yang et al 2015). Furthermore, the presence of clay lenses in sand aquifers affects subsidence rates by delaying compaction response to groundwater pumping (Budhu and Adiyaman 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, the deformation of soil skeleton and the groundwater flow are more complex than those in the one‐dimensional (1D) case. Consequently, the fully coupled 3D land subsidence models were studied and applied to investigate the horizontal and vertical displacement and the pore water pressure of aquifer systems (Burbey ; Kihm et al ; Yang et al ). These models considered both aquitard and aquifer units as elastic materials.…”
Section: Introductionmentioning
confidence: 99%